"It's what we perceive as different": an interpretative phenomenological analysis of Nigerian women's characterization of their health during the COVID-19 pandemic - Mary Ndu; Gail Teachman; Janet Martin; Elysee Nouvet (BMC, 2024)
Abstract Background Health has historically been adversely affected by social, economic, and political pandemics. In parallel with the spread of diseases, so do the risks of comorbidity and death associated with their consequences. As a result of the current pandemic, shifting resources and services in resource-poor settings without adequate preparation has intensified negative consequences, which global service interruptions have exacerbated. Pregnant women are especially vulnerable during infectious disease outbreaks, and the current pandemic has significantly impacted them. Methods This study used an interpretive phenomenological analysis study with a feminist lens to investigate how women obtained healthcare in Ebonyi, Ogun, and Sokoto states Nigeria during the COVID-19 pandemic. We specifically investigated whether the epidemic influenced women's decisions to seek or avoid healthcare and whether their experiences differed from those outside of it. Results We identified three superordinate themes: (1) the adoption of new personal health behaviour in response to the pandemic; (2) the pandemic as a temporal equalizer for marginalized individuals; (3) the impacts of the COVID-19 pandemic on maternal health care. In Nigeria, pregnant women were affected in a variety of ways by the COVID-19 epidemic. Women, particularly those socially identified as disabled, had to cross norms of disadvantage and discrimination to seek healthcare because of the pandemic's impact on prescribed healthcare practices, the healthcare system, and the everyday landscapes defined by norms of disadvantage and discrimination. Conclusion It is clear from the current pandemic that stakeholders must begin to strategize and develop plans to limit the effects of future pandemics on maternal healthcare, particularly for low-income women.